Bcl6 Is Required for Somatic Hypermutation and Gene Conversion in Chicken DT40 Cells. - Alan M Williams; Yaakov Maman; Jukka Alinikula; David G Schatz (PLoS ONE, 2016)
The activation induced cytosine deaminase (AID) mediates diversification of B cell immunoglobulin genes by the three distinct yet related processes of somatic hypermutation (SHM), class switch recombination (CSR), and gene conversion (GCV). SHM occurs in germinal center B cells, and the transcription factor Bcl6 is a key regulator of the germinal center B cell gene expression program, including expression of AID. To test the hypothesis that Bcl6 function is important for the process of SHM, we compared WT chicken DT40 B cells, which constitutively perform SHM/GCV, to their Bcl6-deficient counterparts. We found that Bcl6-deficient DT40 cells were unable to perform SHM and GCV despite enforced high level expression of AID and substantial levels of AID in the nucleus of the cells. To gain mechanistic insight into the GCV/SHM dependency on Bcl6, transcriptional features of a highly expressed SHM target gene were analyzed in Bcl6-sufficient and -deficient DT40 cells. No defect was observed in the accumulation of single stranded DNA in the target gene as a result of Bcl6 deficiency. In contrast, association of Spt5, an RNA polymerase II (Pol II) and AID binding factor, was strongly reduced at the target gene body relative to the transcription start site in Bcl6-deficient cells as compared to WT cells. However, partial reconstitution of Bcl6 function substantially reconstituted Spt5 association with the target gene body but did not restore detectable SHM. Our observations suggest that in the absence of Bcl6, Spt5 fails to associate efficiently with Pol II at SHM targets, perhaps precluding robust AID action on the SHM target DNA. Our data also suggest, however, that Spt5 binding is not sufficient for SHM of a target gene even in DT40 cells with strong expression of AID.